Knowledge Management System Dalam Penanganan Stunting oleh Tenaga Kesehatan Kota Bengkulu - Sri Handayani; Yulia Darnita; Rozali Toyib (Jurnal Media Infotama, 2025)
Stunting is a big problem because Stunting is not only related to height but is comprehensive which includes the child's physical condition but is related to the child's ability to learn, mental retardation, and susceptibility to chronic diseases that will affect the quality of human resources in the future. create a Knowledge Management System (KMS) model for the handling community so that the knowledge possessed by community members can be used by other community members. Knowledge Management System (KMS) is a system in processing knowledge, the use of Content Management System (CMS) php Bulletin Board (phpBB) as a basis for supporting a discussion forum between farmers to exchange their knowledge of processed products, Conclusion The knowledge of mothers of toddlers is lacking about nutrition (40.4%) stunting occurs, Exclusive Breastfeeding (45.5%) stunting and Sanitation Hygiene (55.6%) stunting affects the rate of stunting in toddlers, Knowledge Management System for Community health workers can be used by the community to create, process, and distribute knowledge to all community members.